Adult neurogenesis promotes balance recovery after vestibular loss. (March 2019) - Tighilet, Brahim; Chabbert, Christian
Highlights: Unilateral vestibular neurectomy in the adult mammal induces intense cell proliferation in deafferented Vestibular nuclei. Most of newborn cells survive up to 1 month, differentiate into different cell types and contribute to functional recovery. Reactive vestibular neurogenesis is a new contributor to the repair of adult damaged brain. This model does not belong to the canonical neurogenic niches, but it is the best example so far of reparative role of adult neurogenesis. These results open new medical perspectives for the therapy of vestibular disorders. Abstract: A phenomenon called vestibular compensation occurs after peripheral vestibular loss. This process involves a mosaic of profound structural rearrangements within the vestibular nuclei. Among them, adult reactive neurogenesis is perhaps the most unexpected, as it occurs in a brain area that was never reported as neurogenic before. Both the survival and functionality of this newly generated neuronal network depend on its integration into preexisting networks in the deafferented structure. Far from being aberrant, this organization allows the brain to use inputs from other sensory modalities to facilitate the restoration of posture and equilibrium. This is the best example so far of the reparative role of adult neurogenesis. Recent findings show that a similar phenomenon exists in other brain sensory structures, such as auditory brain stem nuclei and sensory motor cortex. This raises questions about the putative functional relevance of the reactive neurogenesis.